Materials and sustainable development - Ashby, M. F. (Butterworth-Heinemann, 2024)
Materials and Sustainable Development, Second Edition, written by noted materials selection authority Mike Ashby, provides a structure and framework for analyzing sustainable development and the role of materials in it. The book's aim is to introduce ways of exploring sustainable development to readers in a way that avoids simplistic interpretations and approaches complexity in a systematic way. There is no completely 'right' answer to questions of sustainable development, instead, there is a thoughtful, well-researched response that recognizes concerns of stakeholders, conflicting priorities, and the economic, legal and social aspects of the technology and its environmental legacy. The intent of the book is not to offer solutions to sustainability challenges but rather to improve the quality of discussion and enable informed, balanced debate. This updated edition has been updated to reflect new insights, regulatory trends and other developments that have occurred since publication of the previous edition.